Kurzia trichoclados (Lepidoziaceae, Marchantiophyta)—A disjunct liverwort newly reported for India - Rawat, K.k.; Sahu, Vinay; Verma, P.k.; Asthana, A.k. (Phytotaxa, 2016)
Kurzia trichoclados (K. Müller) Grolle, is a disjunct liverwort known from Europe, North America and Southeast Asia. Its distribution in South Asia has now been expanded to include India.